Triathlon Wet Suit and technical parameters at the start and and of a 1500-m swim - Perrier, D.; Monteil, K. (Journal of Applied Biomechanics, 2004)
The aim of this study was to determine the effect of wearing a triathlon wet suit on the technical parameters of the front crawl stroke. Eight highly trained male triathletes were filmed with underwater camcorders during two 1500-m swim tests: one with a wet suit (WS) and the other with a standard suit (SS). Two conditions were considered: Condition I (CI) and Condition XV (CXV), representing the 1st and the 15th 100-m, respectively. Views were synchronized and digitized using kinematic analysis software (Schleihauf, 1994) to obtain 3-D coordinates of the anatomical landmarks of the body. Results showed that the wet suit and duration of the exercise significantly influenced stroke parameters. The swim with WS was characterized by greater stroke length and a progressive increase in stroke frequency, resulting from a more extended elbow position during the stroke and from a decrease in the absolute and relative times of the propulsive phase. These changes indicated more efficient upper limb action. The duration of exercise modified the swim with WS and SS. The loss of velocity observed in CXV was related to a decrease in stroke length, or more precisely a reduction in lever arm length during the aquatic phase, insufficiently offset by a slight increase in stroke frequency. These two motor responses, a less extended elbow position and a stroke frequency increase, emerged as an easier motor solution for coping with the effect of fatigue. This solution could be regarded as an adaptation to the duration of the exercise.